Art and institutions of power: Fernando Sanchez Castillo's Arquitectura para el Caballo. Issue 2 (1st June 2015) - Gessert, Rebecca
This article models the practice of connecting an artwork to politics, economics, current events and social theory. Basic pictorial elements of Fernando Sanchez Castillo's short colour video Arquitectura para el Caballo (2002) are discussed in a Marxist framework as representations of capitalist ideology. The article supports the relevancy of Castillo Sanchez's work in the context of recent anti-austerity protests in Spain, surveys other works by Castillo for themes of power, riot and suppression of riot, briefly discusses architecture and its role in controlling human behaviour and relates Arquitectura to questions surrounding the role higher education plays in supporting capitalist ideology. In the end, the article concludes that Castillo's work predominantly functions to critically spotlight the normalization of institutions like riot police and the educational system.